Candida auris: emergence and epidemiology of a highly pathogenic yeast - Santos, Paula Slomp; Lana, Daiane Flores Dalla; Mezzari, Adelina (Clinical and Biomedical Research, 2017)
Candida auris is a multidrug-resistant emerging yeast, which was responsible for healthcare-associated infection outbreaks, and was cataloged as a new species in 2009, after being isolated from a patient’s ear canal secretion in Japan. Since the notification of this first occurrence, numerous cases have been reported throughout the world, including Brazil. C. auris affects mainly inpatients, patients in intensive care units, exposed to broad-spectrum antifungal medications and who make use of vascular catheters. Currently, this yeast is one of the main responsible for invasive infections in hospitals and has been cause of concern by authorities and organs due to its rapid dissemination and difficult treatment caused by its low susceptibility to antifungal agents traditionally used in clinical practice. As a contributor to the severity of infections associated with C. auris, the transmission mechanism is still unknown, which implies in a lack of control of the microorganism and high mortality rates. Thus, this literature review presents relevant information in order to alert the importance of C. auris as an etiological agent of systemic infections, as well as its epidemiology and the real challenges of the treatment. Keywords: Candida auris; candidiasis; candidemia; multidrug-resistance; biofilm; epidemiology; diagnosis